Assessment of Challenges and Opportunities in Private Forest Management in Sarlahi District, Madhesh Province, Nepal - Pramod Ghimire (Contemporary Research: An Interdisciplinary Academic Journal, 2026)
Private forests in Nepal are gaining recognition as a vital component of forest resource management, contributing significantly to timber production, environmental services, household income, and environmental services. This study analyzed the challenges and opportunities of Private forests (PFs) management in the Sarlahi district of Madesh Province, Nepal. The study was conducted covering all 91 registered Private forest owners, using questionnaire surveys, group discussions, and field observations. Results found that Private Forest ownership was primarily held by male (76.92%), with most owners aged between 41 and 50 years. Agriculture was the primary source of income for more than half of the participants (52.74%). The composition of species in Private forests was primarily made up of fast growing and economically important species, including Eucalyptus camaldulensis (34%), Tectona grandis (21%), and Dalbergia sissoo (16%). The developmental trend indicated steady growth in registered private forests from 1990 to 2010, followed by a decline after 2010 due to complicated regulatory procedures. Furthermore, study found that complicated harvesting permits, transportation restrictions, and lack of financial incentives were the major challenges perceived by forest owners. Conversely, income generation, livelihood diversification, and the local security of forest products were recognized as essential opportunities. Despite its strong economic potential, Private forestry in the Terai region faces significant institutional barriers that limit its expansion. Policy reforms, streamlined regulations, improved market access, and technical support can strengthen Private forestry’s role in sustainable forest management and rural livelihoods in Nepal.